Gastronomy as a form of cultural tourism: A Greek typology - Moira Polyxeni; Mylonopoulos Dimitrios; Kontoudaki Aikaterini (University Educons, Faculty of Sports and Tourism, Novi Sad, 2015)
Foods, as well as other factors, such as accommodation, attractions, recreational activities and transport are key parts of the tourism product of host destinations. It has been found that in recent years, tourism choices have not been determined only by the simple biological need to eat, but also by the desire to try interesting products within an appropriate environment. Modern, experienced travelers look for destinations' quality, as linked to a deeper knowledge of the culture and lifestyle of the inhabitants of the place they are visiting. As lifestyles of people are deeply related to what and how they eat, how they prepare food and in what environment, what the rituals of food consumption are, combined with the architecture and place, a strong demand has been created for local food and a trend of what is called 'gastronomic/culinary tourism'. A survey was carried out in order to explore the forms of product supply, commercialization strategy as well as methods to promote gastronomic tourism in Greece. In particular, the search was carried out through the internet businesses in Greece involved in the field of gastronomy and tourism, using keywords such as gastronomy, Greek cuisine, Greek breakfast, wine routes, olive routes, etc. Then, the findings were classified into categories in order to evaluate their activity. The survey revealed that companies involved in the field of gastronomy are numerous and of various nature. These include restaurants, hotels, guest and rural houses, tourism agencies, food manufacturers, food markets, museums, exhibition halls, etc. Their activities are equally varied and creative (related to wine, honey, herbs, etc, cultural routes that have to do with a product, thematic museums, etc). Due to the lack of targeted central tourism policy in the field, it is proposed to further explore the field and record domestic gastronomic resources at regional administrative levels in order to effectively valorize and promote them with a view to establishing each region as a distinct gastronomic destination.